Histochemical and structural characterization of egg extra‐cellular matrix in bufonid toads, Bufo bufo and Bufotes balearicus: Molecular diversity versus morphological uniformity. Issue 11 (5th August 2014) - Mentino, Donatella; Mastrodonato, Maria; Rossi, Roberta; Scillitani, Giovanni
ABSTRACT The extra‐cellular matrix of fertilized eggs in the bufonid toads Bufo bufo and Bufotes balearicus was studied to clear the relationships between structural and molecular diversity. Histochemical (PAS, AB pH 2.5 and pH 1.0, Beta‐elimination PAS) and lectin‐histochemical (Con A, WGA, Succinyl‐WGA, PNA, RCA‐1, DBA, SBA, AAA, UEA‐I, LTA) techniques were used and the observations were made under light and electron microscopy. Both species present a fertilization envelope (FE) and two jelly layers (J1 and J2). The fibers of J2 are shared among the eggs of a clutch in a jelly ribbon. The FE of both species presents neutral glycoproteins, mostly N‐linked. In B. bufo there are also residuals of mannose and/or glucose and N‐acetylglucosamine. In the FE fibers run parallel to egg's surface or are in bundles or looser hanks with no clear orientation. The J1 layer of both species presents sialosulfoglycoproteins, mostly O‐linked, with lactosaminylated, galactosaminylated, glycosaminylated, and fucosylated residuals. A lower amount of galactosaminylated residuals is observed in B. balearicus in respect to B. bufo, whereas the opposite is seen in the amount of fucosylated residuals. The J2 layer is similar in composition to J1 but in B. balearicus there are no glucosaminylated residuals. J layers present fibers and granules that reduce towards J2. Several microorganisms, in particular blue algae, are observed in the J2 layer of both species. In respect to other species, B. bufo and B. balearicus have a lower number of jelly layers, but a comparable number of glycan types. Microsc. Res. Tech. 77:910–917, 2014. © 2014 Wiley Periodicals, Inc.